Calving driven by horizontal forces in a revised crevasse-depth framework - D. A. Slater; T. J. W. Wagner (The Cryosphere)
Calving is a key process for the future of our ice sheets and oceans, but representing it in models remains challenging. Among numerous possible calving parameterisations, the crevasse-depth law remains attractive for its clear physical interpretation and its performance in models. In its classic form, however, it requires ad hoc and arguably unphysical modifications to produce crevasses that are deep enough to result in calving. Here, we adopt a recent analytical approach accounting for the feedback between crevassing and the stress field at floating ice shelves, and we generalise the framework by adding non-zero ice tensile strength and basal friction and by applying it to grounded marine-terminating glaciers. We show that the revised formulation removes the need for ad hoc modifications and predicts that full-thickness calving should occur when grounded glaciers reach flotation, provided the calving front ice thickness is greater than around 400 m. The revised formulation also predicts no calving for ice thinner than around 400 m, suggesting that calving at such glacier fronts is not driven purely by horizontal forces. We find good observational support from both grounded marine-terminating glaciers and floating ice shelves for this analysis. We advance the revised crevasse-depth formulation as a step towards understanding differing calving styles and a better representation of calving in numerical models.